Analysis of Internal Community Factors in Participating in the Family Planning Program in Medan Johor District Using the Logistic Regression Method - Hardiyanti, Siska; Darnius, Open; Sitepu, Israil; S, Benar (Journal of Research in Mathematics Trends and Technology, 2023)
Regression is a statistical analysis method to describe the relationship between the dependent variable which has two or more categories with one or more independent variables on a categorical or continuous scale. The purpose of this study is to apply the logistic regression method to see how much influence the Internal Factor Analysis of the Community has in participating in the Family Planning Program in Medan Johor District. As is known, according to data from the BPS for North Sumatra Province, Medan Johor is included in a slum sub-district because it is caused by the dense population in this sub-district which is not in accordance with its area. The total population in Medan Johor District currently reaches 137,367 people, with an area of 16.96 km2and a population density of 8,099 people/km2. So that in this study, it was found that the level of education, age and occupation did not have a significant effect on opinion, which had a significant effect on opinion with a Sig value of 0.020 <0.05, namely the community's knowledge of the family planning program